Healthy behavior among students with learning difficulties from the point of view of their mothers (Journal of the College of Basic Education, 2022)
The issue of healthy behavior is of increasing importance, not only in terms of physical aspects, but also in psychological aspects. These days there are many of these risks that the child places himself in, so he eliminates himself and his health and based on that, the current research aimed at 1- Identifying healthy behavior among students with learning difficulties. 2- Identifying the differences in healthy behavior according to the type variable ( Male-female) The current research was limited to a sample of students with learning difficulties and learners in primary schools in Baghdad and affiliated to the first directorate of education of Karkh and both sexes and for the academic year (2018-2019), and the current research sample reached (124) male and female students, and to achieve the research goals The current researcher The researcher has prepared a measure that includes (29)after being presented to a group of experts in education and psychology and subjecting its paragraphs to statistical analysis, where it became in its final form consisting of (29) paragraphs. After applying the scale to the research sample and analyzing the data, the results of the research appeared as follows: -Students with learning disabilities have a low level of healthy behaviorThere are no significant differences in healthy behavior between males and females.Based on the results of the research, the researcher developed a number of recommendations and proposals.